The relationship between implicit motives and physical activity: a scoping review - Julian Brummer; Nikkil Sudharsanan; Martin G. Köllner (Systematic Reviews, 2024)
Abstract Background Interventions that leverage implicit motives — affect-based, non-conscious motivational dispositions — may increase physical activity by making physical activity more pleasurable. However, there is no evidence synthesis of the empirical data linking the major implicit motives (achievement, affiliation, and power motives) and physical activity. We aimed to close this research gap. Methods Following a systematic literature search in the PsycInfo, PubMed, and Web of Science databases until August 2024, we performed a scoping review. We included German- or English-language publications in peer-reviewed journals or books that followed an observational or intervention study design. Studies had to link ≥ 1 major implicit motive measured via a well-established method to physical activity behavior. We critically appraised the methodological quality of the included studies using an adaptation of the JBI critical appraisal checklist for analytical cross-sectional studies and synthesized the evidence qualitatively. Results Out of 1047 potentially relevant records, five publications (seven studies, N = 550) were included. All eligible studies were observational (six cross-sectional, one prospective longitudinal). The achievement motive was researched the most. The data indicated a relatively consistent positive association between physical activity and the achievement motive, particularly in athletes and in sports-specific settings. The associations with the affiliation and power motives were more mixed. Most studies were conducted in sports-specific settings. All studies elicited methodological concerns, to varying degrees. Conclusions The available data indicate a positive association between achievement motive strength and physical activity. However, important limitations, especially the lack of intervention studies and the use of non-gold standard assessment methods, limit the confidence in the findings. More, methodologically sound research is needed to better understand the link between implicit motives and physical activity, especially in the general population. Systematic review registration PROSPERO CRD42023392198.